ANTIOXIDANTS ACTIVITY OF FLAVONOID METABOLITES CAUSED BY THE HUMAN GUT MICROFLORA - Surco-Laos, Felipe (2016)
Flavonoids and more phenolic compounds when ingested are metabolized to phenolic acids, which are classified as benzoic, phenylacetic and cinnamic primarily, by “in vitro” methods (ABTS and FRAP), the antioxidant capacity of phenolic acids of potential metabolic interest was determined. The values vary by chemical reaction involved and the structure of the compounds, which influences the number of radicals, their position on the benzene ring relative to the carboxylic group and the chain length of the latter. In interactions between mixtures of acids a mainly antagonistic effect is observed, there is no structural pattern that explains it.